THE INFLUENCE OF MARBLE SCIENCE’S AUDIO-VISUAL MEDIA: HUMAN ANATOMY ON ELEMENTARY SCHOOL STUDENTS’ LEARNING INTEREST - Awalina Barokah; Fitriyani; Sonia Devi Nopriastuti; Muhammad Irsyad (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the influence of the use of Marble Science’s audio-visual media on Anatomy on elementary school students’ learning interests. The research used pseudo[1]experimental research with a nonequivalent comparison-group design. Data collection was carried out with a questionnaire of students' learning interests that had been tested for validity and reliability. Data analysis used Univariate Analysis of Variance with a significance level of 5%. The research results indicate that the difference in the average score of the pre-test was 66.00 while the average post-test score of students’ learning interest was 89.50. Marble Science’s Audio-Visual Media of Human Anatomy has a significant and positive effect on students' interest in learning seen from the Tcount of 14.85 and P of 0.000, which means P = 0.000<0.05. Researchers recommend the use of Marble Science’s Audio-Visual media on human Anatomy can be used to improve the students’ learning outcomes, learning motivation, and critical thinking skills.